Is The Test Sensible? Developing A Critical Reading Test for Indonesian EFL Learners - Ary Setya Budhi Ningrum; Emy Sudarwati (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2022)
This study aims at developing a critical reading test for Indonesian EFL students. This (R & D) project is intended to assess students' progress and is supposed to offer accurate and trustworthy results. The subjects were twenty students from the English Language and Literature Department at Brawijaya University who took part in the try out stage. The test items' difficulty indices ranged from 0.26 to 0.89. The reliability coefficient for the KR-20 was determined to be 0.95, indicating that this multiple-choice critical reading comprehension test is valid and reliable. Despite of the fact that the Critical Reading test is declared valid and reliable, the students’ score taking the Critical Reading test during the try out is less satisfactory. This might be caused by limited number of students taking the try out or problems dealing with teaching and learning process of critical reading in the classroom causing students’ inability to do the test well. Future researchers are suggested to address this issue by either involving more participants during the try out to get the reasons underlying students lack of ability in doing critical reading test.